Síntese e caracterização de géis da reação álcali-sílica em condições aceleradas - Almeida, Thiago da Silva (2015)
In the concrete pathology area several mechanisms are responsible for submitting cracking frames. Either by mechanical electrochemical or geochemical phenomena, the appearance of cracks is quite common in many structures. However among the various processes that can lead to excessive cracking we highlight the corrosion of armor, the attack by intrinsic or extrinsic sulfate (ettringite). The alkali-aggregate reaction (AAR) in turn has achieved prominence recently especially the powers given to buildings in the city of Recife with severe damage to the structure. This phenomenon is complex although the scientific knowledge around the topic is abundant the Brazilian standard is recent. Known for over 60 years in technical means it is known that this reaction is generally slow and involves alkalis from the cement and some mineralogical constituents of the aggregates. The product of this reaction is a hygroscopic gel which on contact with water swells considerably which in addition to cause a cracking process in concrete structures also generates the triggering of other pathological manifestations due to ingress of aggressive agents that they spread the cracks. Thus various accelerated tests have been used for the diagnosis of susceptibility of aggregates throughout the world. In practice it is common to observe the occurrence of conflicting results generating false negative in some cases. In this sense there is still need to improve knowledge on the effects of testing conditions accelerated in the microstructure thermodynamics and kinetics of the reaction of forming AAR gels. So this thesis aims to synthesize under controlled conditions of laboratory AAR gels from amorphous nature of aggregates (Pyrex) and crystalline (granite gravel) through the evolution of the microstructural characteristics of the gels the temperature is varying the molarity and the type alkali. For production of AAR gels were used and three Pyrex the granite aggregate mixed with solutions of NaOH 1M and 3M KOH and the mixture of both NaOH and KOH 3M and reaction process cues in the 20 °C temperature 40 °C 60 °C and 80 °C for 28 days during this reaction process the pH of the solutions were monitored. After the process of reaction all raw materials and RAA gels produced undergone an advanced microstructural characterization making the use of techniques such as XRF, SEM, XRD, FTIR and TGA / DTA. The results showed that both the temperature increase as the molarity accelerate the reaction kinetics for formation of gels RAA with increasing molarity contribute more significantly. The XRD indicated phase transformations both in the amorphous system as in the lens and the emergence of new crystalline phases rich in sodium (Trona, Natron and Termonatrite). In the lens system it was found that the phase that most contributed to the formation of AAR gels was mica. And mica rich gravel in the Muscovite type are more reactive than gravel rich in mica-type biotite. The thermal analysis and FTIR showed that the gravel rich in Muscovite mica type are not only more reactive but also contribute to the formation of gels combined with water in its structure. With respect to the type of alkali results showed that the type of alkali influences not only the type of gel formed and also the amount of gel produced, where K-type systems containing alkali AAR showed a higher production capacity gels compared with alkali systems of the type Na or the mixture of Na and K. The results also show that gels formed of AAR in alkaline solutions in the presence of Na and K showed more combined water in their structure when compared to gels produced from solutions with Na and K alkali separately.